Kemampuan Jamur Akar Putih (Rigidoporus microporus (Swartz: Fr.) Van Ov.) dalam Mendegradasi Limbah Selulosa - Dianty Putri; Nasril Nasir; Anthoni Agustien (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2019)
Cellulose is one of abundance natural biopolymer with limited usage. The common found waste cellulose are waste straw, sawdust, and pineapple pit. Rigidoporus microporus is a white root fungi groups that often attack the roots of plants that rot and die. This study was conducted to assess the ability of white root fungi (R. microporus) to degrade waste cellulose, according to cellulolitic activity index of potential R. microporus isolate. The medium used was Carboxy Methyl Cellulose (CMC) with dye Congo Red (0,1%). The results obtained that R. microporus has cellulotic index 3,23 which indicated as potential cellulose degrade.